Arabic language-learning strategy preferences among undergraduate students - Brosh, Hezi Y. (Studies in Second Language Learning and Teaching, 2019)
This study elicited Arabic students’ perceptions regarding their language-learning strategy preferences (LLSPs). A sample of 120 undergraduate Arabic students participated. Data were collected through a questionnaire and interviews. The findings reveal that students tend to adopt a holistic view of the learning task and relate it to real-life, personal experience. Participants selected interaction with the teacher, speaking, and flashcards as their most preferred application-directed learning strategies. These selections demonstrate that Arabic students desire to be proactive in order to make the language more concrete for them, to enhance their performance, and to develop language skills that will last a lifetime. Whereas advanced level participants preferred interaction with the teacher, speaking, flashcards, and working individually, beginner level participants preferred learning grammar and group work. The empirical evidence from this study could have implications regarding theoretical models of effective Arabic language instruction, Arabic teacher education programs, and curriculum development.